The Initial Performance of IPOS:Further Evidence from Bursa Saham - Lin, Sia Peng (2005)
There has been much empirical and theoretical literature documenting underpricing phenomena in IPO, especially on the first day trading. This study attempts to provide the initial performance of IPOs listed on the Main Board and Second board of Bursa Malaysia over the period from 2000 to 2004 and the factors that could influence the underpricing level are examined. The entire sample of 181 IPOs are selected to test the effect of the relationship on the first day raw initial return and market adjusted initial return in Malaysia. Results show level of underpricing with raw average initial return of 30.80% and 30.78% for adjusted average initial return, both of the average returns appear substantially lower than the earlier studies done on Malaysian stock market. Next, the investigation on ex-ante uncertainty relationship with the underpricing level can be proven significantly in this study by using the Second Board IPOs as the proxy. Further, the Demand (Oversubscription ratio), IPO Method by Public Issue are also significant affected the underpricing level in the study. Conversely the Market Climate, Underwriter Reputation, Technology IPO and size of Gross Proceeds do not have significant impact on the level of the initial returns. Four regression models are tested and results reveal that all these variables do have some explanatory power to the models in determine the underpricing with at least 16% of variation in the degree of undepricing found. In addition to that, in this study I observe there are significant relationship between the Market Climate and Demand.